Comparison of the efficacy of skin examination using 3D total body photography to clinical and dermoscopic examination - Frank Friedrich Gellrich; Anne Strunk; Julian Steininger; Friedegund Meier; Stefan Beissert; Sarah Hobelsberger (EJC Skin Cancer)
Background: Non-melanoma skin cancer (NMSC) is the most common malignant tumor that poses a worldwide problem for health services. Three-dimensional total body photography (3D-TBP) is currently used as an adjunct to skin examination, particularly to monitor melanocytic lesions in patients at high risk of melanoma. Objectives: The authors investigate the efficacy and limitations of a skin examination for NMSC performed solely with 3D-TBP without patient contact. Methods: 130 patients with 167 skin lesions with suspected NMSC underwent skin examination with dermoscopy and subsequent surgery. In addition, a 3D-TBP was performed, which was subsequently assessed by an independent dermatologist and compared with the initial skin examination and histological findings. Results: Using 3D-TBP, a significantly lower sensitivity for the diagnosis of BCC (0.44 vs 0.77), a lower sensitivity for SCC (0.70 vs 0.78; p=0.754) and a significantly lower sensitivity for invasive skin tumors overall (0.66 vs 0.88; p<0.001) was achieved compared to clinical skin examination with dermoscopy. The location of the skin tumor did not influence the effectiveness of 3D-TBP. More advanced skin tumors with a greater tumor thickness (p<0001) or a higher infiltration level were detected more frequently with 3D-TBP (p=0.001). Conclusion: The results of this study show that 3D-TBP alone is inferior to traditional skin examination with dermoscopy. However, more advanced NMSCs were more likely being detected with 3D-TBP. Further studies need to investigate whether the effectiveness of 3D-TBP alone can be improved by using additional photographs of poorly visible areas of the body or digital dermoscopy.